(untitled) (Revista Contexto & Educação, 2022)
This article addresses the subject of Global Citizenship Education (GCE) as a pedagogical approach. To this end, it analyzes the evolution of the concept of citizenship from Anvient Greece to the integration of civil, political and social rights in the contemporary age, as well as presents different understandings on the phenomenon of globalization, entering into the debate about the concept of global citizenship and its premises. It analysis the critiques posed to GCE by researchers in education regarding its conceptual approach and applicability, especially in the field of teacher education. It addresses the model of GCE proposed by UNESCO and the legal framework for curriculum in teacher training in Brazil. Based on the main criticisms in the field of GCE, this article assesses the challenges to build itself as a critical and progressive pedagogical approach, far from a redemptive or consumerist model of education.